Pengayaan sumber belajar sejarah berbasis situs cagar budaya ragawi di Kabupaten Sidoarjo - Reza Hudiyanto; Ismail Lutfi; Ronal Ridhoi (Jurnal Praksis dan Dedikasi Sosial, 2026)
Enrichment of history learning resources based on the ragawi cultural heritage site in Sidoarjo Regency Sidoarjo Regency possesses a wealth of tangible cultural heritage sites ranging from the Classical to the Colonial era, offering significant potential as history learning resources. However, this potential has not been optimally utilized in school learning due to the lack of valid teaching materials and limited accessibility of academic references for teachers. This community service activity aims to enhance teachers' competence in utilizing lokal sites as learning media through the development of research-based teaching materials. The implementation method employs a participatory approach with the Musyawarah Guru Mata Pelajaran (MGMP) of Senior High Schools (SMA/SMK/MA) in Sidoarjo Regency as the partner. The activity series includes Focus Group Discussions (FGD) for needs analysis, workshops on archaeological knowledge transfer, and intensive mentoring for book manuscript drafting. The results show an increased understanding among teachers regarding the historiography and archaeological data of Candi Pari, Candi Sumur, and colonial industrial buildings. The main output of this program is the compilation of a draft titled "Cultural Heritage Site-Based History Learning for High-School," specifically designed as enrichment material for students. This program concludes that collaboration between academics, the designation of cultural heritage buildings in Sidoarjo Regency" and educational practitioners is effective in bridging the gap between scientific archaeological data and the practical needs of history learning in schools. Kabupaten Sidoarjo memiliki kekayaan situs cagar budaya ragawi (tangible heritage) dari masa Klasik hingga Kolonial yang potensial sebagai sumber belajar sejarah. Namun, potensi ini belum dimanfaatkan secara optimal dalam pembelajaran di sekolah karena minimnya ketersediaan bahan ajar yang valid dan aksesibilitas referensi akademis bagi guru. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi guru dalam memanfaatkan situs lokal sebagai media pembelajaran melalui penyusunan materi ajar berbasis riset. Metode pelaksanaan menggunakan pendekatan partisipatoris dengan mitra Musyawarah Guru Mata Pelajaran (MGMP) Sejarah SMA/MA Kabupaten Sidoarjo. Rangkaian kegiatan meliputi Focus Group Discussion (FGD) analisis kebutuhan, lokakarya transfer pengetahuan arkeologis, dan pendampingan intensif penyusunan naskah buku. Hasil kegiatan menunjukkan adanya peningkatan pemahaman guru terhadap historiografi dan data arkeologis situs Candi Pari, Candi Sumur, serta bangunan industry gula masa kolonial. Luaran utama dari program ini adalah tersusunnya draf buku "Pembelajaran Sejarah berbasis Situs Cagar budaya untuk Sekolah Menengah Atas" yang dirancang khusus sebagai materi pengayaan bagi siswa. Program ini menyimpulkan bahwa kolaborasi antara akademisi dan praktisi pendidikan efektif dalam menjembatani kesenjangan antara data ilmiah arkeologi, hasil penetapan bangunan cagar budaya Kabupaten Sidoarjo dengan kebutuhan praktis pembelajaran sejarah di sekolah.